Hanya Orang Sukses yang Tahan Dalam Proses - Damayanti Nababan; Sarah Simanjuntak; Ferdianto Hutagalung; Keybran Situmeang; Elsah Rosianna Lumban Tobing; Flora Cristiani Hutapea; Lembang Yanatio Situmeang (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
This Community Service was conducted to motivate and build students' enthusiasm in achieving their goals and achievements in the process. This research was conducted using the action research (Action Research/AR) research method as a form of direct action in solving problems. It is very important to include God in our faithful process so that we can endure the existing process.